Farm health in times of corona: Govt must ensure the agri supply-chain remains uninterrupted - Verma, Smriti; Kumar, Anjani; Padhee, Arabinda K. (Indian Express Group, 2020)
The evolving situation around Covid-19 is becoming critical. Governments have already announced guidelines for citizens to keep themselves safe. Packages have also been declared to safeguard interests of various sectors. What could be the possible fall out on the agriculture sector—50% of population still depends on it—is indeed a cause of concern.